Analyzing the New War Concept with the Context of 11 September Attacks and Terrorism - Güntay, Nükhet (Fırat Üniversitesi, 2023)
The terrorist attacks to the World Trade Centre in New York and the Pentagon in Washington DC on September 11, 2001 reinforced comments that it was the beginning of a new era. In the 21st century, war and terrorism exert increasing power in international affairs and are accepted as sources of destabilization of international security. In this regard, concept of “new war” is on the agenda of international relations and terrorism is evolving in a new direction in this process. In this study, it aims to reconsider the development process, transformation, and important moments in the history of international relations in order to explain the new concept role played by terrorism on a global basis. In this context, the dimension of the reflection of terrorism in term of the transformation of the concept of new war in international relations is discussed by using the case study method and the September 11 attacks and the subsequent process. The determinations and the conclusion are related to the continuity of the phenomenon of terrorism within the concept of new war. Different border and international conflicts also show that terrorism is among the main factors that will feed different problems. Likewise, within the scope of this study, terrorism, as seen on September 11, shows that war has a moer destructive and threatening potential and that war is shaped according to the new order rather than traditional methods.

11 Eylül 2001’de teröristlerin New York’taki Dünya Ticaret Merkezi’ne ve Washington DC’deki Pentagon’a saldırısı, yeni bir dönemin başlangıcı olduğu yönündeki yorumları kuvvetlendirmiştir. 21. yüzyılda savaş ve terörizm, uluslararası meselelerinde artan bir güç uygulamakta ve uluslararası güvenliğin istikrarsızlaşmasının kaynakları olarak kabul edilmektedir. Bu bağlamda “Yeni Savaş” kavramı uluslararası ilişkiler gündeminde bulunmakta ve terörizm de bu süreç içerisinde yeni bir yöne doğru evrilmektedir. Bu çalışma, yeni savaş kavramı ve terörizmin küresel bazda oynadığı kalıcı rolü açıklamak için uluslararası ilişkiler tarihindeki gelişim süreci, dönüşümü ve önemli anları yeniden ele almayı amaçlamaktadır. Bu kapsamda örnek olay yöntemi kullanılarak 11 Eylül saldırıları ve sonraki süreç akademik çalışmalar incelenmesiyle ele alınarak uluslararası ilişkilerde yeni savaş kavramının dönüşümü açısından terörizmin yansımasının boyutu ele alınmaktadır. Yapılan tespitler ve ulaşılan sonuç yeni savaş kavramı içinde terörizm olgusunun sürekliliği ile ilgilidir. Farklı sınır çatışmaları ve uluslararası anlaşmazlıklar da göstermektedir ki terörizm farklı sorunları besleyecek ana faktörler arasındadır. Keza bu çalışma kapsamında, 11 Eylül’de görüldüğü gibi terörizm, savaşın daha yıkıcı ve tehdit edici bir potansiyele sahip olduğunu ve savaşın geleneksel yöntemlerden ziyade yeni düzene göre şekillendiğini göstermektedir.
11 EYLÜL SALDIRILARI VE TERÖRİZM EKSENİNDE YENİ SAVAŞ KAVRAMININ ANALİZİ